Becoming an open educator: towards an open threshold framework - Tur, Gemma; Havemann, Leo; Marsh, Dawn; Keefer, Jeffrey M.; Nascimbeni, Fabio (Research in Learning Technology, 2020)
In this article, we propose a cross-pollination of two prominent lines of educational thought: open education (OE) and threshold concepts (TCs). Open education has gained an increased profile through the growing popularity of open educational resources (OER) and massive online open courses (MOOCs). Educators who create or make use of such resources, or employ related open educational practices (OEP), are often suggested to have a transformative impact in educational settings. In recent years, educational research has increasingly discussed learning as a process of attaining or crossing certain conceptual thresholds, which involve such a significant shift that the learner eventually achieves a different and deeper understanding of core disciplinary knowledge, even a new identity. Of the eight characteristics of TCs identified in the core literature of this theory, we consider that three in particular offer the maximum potential for understanding the evolution of teachers towards the open educator identity: transformative, troublesome and liminal. This work presents a theoretical framework that includes the transformative impact on identity in the process of becoming an open educator, the troublesomeness inherent in this evolution and the liminal space through which the evolving teachers progress. It is argued that a focus on the development of open educator identity aligns with current reflective approaches to working on teachers’ professional identity, and at the same time supports a focus on teachers’ commitment to a democratic approach to education, which is necessary in neoliberal times.
Keywords: open education; threshold concepts; open educator; teachers’ identity; open educational practices; Scopus; Emerging